Double In situ Hybridization for MicroRNAs and mRNAs in Brain Tissues - Kasai, Atsushi; Kakihara, Sora; Miura, Hiroki; Okada, Ryo; Hayata-Takano, Atsuko; Hazama, Keisuke; Niu, Misaki; Shintani, Norihito; Nakazawa, Takanobu; Hashimoto, Hitoshi (Frontiers in Molecular Neuroscience, 2016)
MicroRNAs (miRNAs) participate in a variety of functions in the brain. Understanding the in vivo localization of miRNAs is an important step for uncovering their roles in brain function. However, the in situ detection of low-abundance miRNAs in brain tissues remains difficult and requires extensive optimization of in situ hybridization (ISH) protocols in individual laboratories. Thus, detailed information regarding experimental conditions would serve as a useful reference for researchers in this field. Here, we investigated and summarized the effects of adjusting a series of critical steps, including tissue fixation, probe accessibility and hybridization stringency, to standardize the currently used miRNA ISH procedures. As a result, we successfully detected several low-abundance miRNAs by ISH using the following experimental conditions: (1) use of fresh brain tissues, (2) digestion of brain samples with proteinase K, (3) LNA-probe hybridization at a temperature 37°C below the melting temperature of the RNA, (4) performance of high-stringency wash steps using 50% formamide in 1× standard saline citrate (SSC) buffer. RT-PCR of the punched-out tissues using TaqManTM primers confirmed the ISH results. Finally, double-fluorescence ISH successfully demonstrated the colocalization of miRNAs and mRNAs. Thus, the detailed information regarding the miRNA ISH procedures used in this study may help to resolve the technical hurdles observed in the in vivo localization of miRNAs, and the elucidation of the specific roles of miRNAs.